Vertical Dynamic Analysis of Ballastless Tracks on Train-Track- Bridge System - Xie Haoran; Yan Bin; Huang Jie (MATEC Web of Conferences, 2020)
In order to investigate the vertical dynamic response characteristics of train-track-bridge system on CWR (Continunously Welded Rail) under dynamic load of train on HSR (High-Speed Railway) bridge. Based on the principle of vehicle train-track-bridge coupling dynamics, taking the 32m simply supported bridge of a section of Zhengzhou-Xuzhou Passenger Dedicated Line as an example, the finite element software ANSYS and the dynamic analysis software SIMPACK are used for co-simulation, and bridge model of the steel spring floating slab track and the CRTSIII ballastless track (China Railway Track System) considering the shock absorbing steel spring, the limit barricade and the contact characteristics of track structure layers are established. On this basis, in order to study the dynamic response laws of the design of ballastless track structure parameters to the system when the train crosses the bridge and provide the basis for the design and construction, by studying the influence of the speed of train on the bridge, the damage of fasteners and the parameters of track structure on the train-track-bridge system, the displacement of rail, vertical vibration acceleration and wheel-rail force response performance are analyzed. Studies have shown that: At the train speed of 40 km/h, the displacement and acceleration of the rail and track slab in the CRTSIII ballastless track are smaller than the floating slab track structure, but the floating slab track structure has better vibration reduction performance for bridges. The acceleration of rail, track slab and bridge increases obviously with the increase of train speed, the rail structure has the largest increasement. Reducing the stiffness of fasteners could decrease the vertical acceleration response of the steel spring floating slab track system, the ability to absorb shock can be enhanceed by reducing the stiffness of the fastener appropriately. Increasing the density of the floating slab can increase the vertical acceleration of the floating slab and the bridge, thereby decreasing the vibration amplitude of the system.